Primary sclerosing encapsulating peritonitis - Swati Mishra; Kuldeep Chaudhary; Swati Tyagi; Pratibha Mishra; Vatsala Misra (Indian Journal of Pathology and Microbiology)
Sclerosing encapsulating peritonitis also known as cocoon abdomen is a rare chronic inflammatory condition of the peritoneum in which the bowel loops are encircled by a membrane (cocoon formation) within the peritoneal cavity leading to intestinal obstruction. It can be primary (idiopathic) or secondary (chemotherapy, beta-blockers, peritoneal dialysis, shunts, tuberculosis, systemic lupus erythematosus, etc.). The symptomatology report includes recurrent episodes of abdominal pain and vomiting. We present here a case of a 32-year-old male who presented with complaints of being unable to pass stools, vomiting (3–4 times), and abdomen pain for 4 days. This case is considered worth mentioning due to its rarity, lack of identification of secondary causes, and diminutive mention of histopathological aspect.